An Analysis of Islamic Boarding School Students’ Understanding of Zakat in Nailur Raja’ - Risal Apriono (ALSYS, 2026)
Although kitab kuning learning has been widely studied in pesantren education, studies that specifically analyze the level of students’ understanding of zakat material in Nailur Raja’ Syarh Matan Safinatun Najah remain limited. This study aims to analyze the level of understanding of students at Minhajul Hayah Islamic Boarding School Tawangmangu regarding zakat material in the book. This study used a quantitative approach with a descriptive survey design involving 17 students through a saturated sampling technique. Data were collected through a written test measuring students’ understanding of the definition of zakat, the obligatory requirements of zakat, types of zakat, nisab, haul, and groups of zakat recipients (mustahik). The data were analyzed using descriptive statistics in the form of percentages and categorization of levels of understanding. The results showed that 70.6% of students were in the high understanding category, whereas 29.4% were in the moderate understanding category. The students’ relatively high level of understanding was supported by the method of memorizing the matan and contextual explanations of the book’s content. However, learning still faced obstacles in the form of less systematic material delivery, limited applicative exercises, and low mastery of Arabic linguistic sciences, particularly nahwu and sharaf. These findings contribute to the development of pesantren pedagogy, particularly in kitab kuning-based fiqh learning. The conclusion of this study emphasizes the importance of systematic learning strategies, applicative exercises, and strengthening Arabic language competence to improve students’ understanding of fiqh material and to serve as a reference for the development of learning in pesantren.